Pembelajaran Mendalam (Deep Learning) dalam Pendidikan IPA: dari Kebijakan Hingga Praktik di Kelas - Al-Qoyyim, Thufail Mujaddid; Nabila, Siti Maulidiya (Pijar Pelita: Journal of Early Childhood Education and Early Childhood Islamic Education, 2025)
21st-century science education requires critical thinking, problem solving, creativity, collaboration, and scientific literacy rather than rote memorization. In Indonesia, the Merdeka Curriculum and the Academic Manuscript on Deep Learning highlight its urgency as a strategy to enhance educational quality and nurture the Profile of Pancasila Students. This article presents a literature review on the concepts, strategies, and challenges of implementing deep learning in science education. Findings indicate that inquiry-based learning, discovery learning, and project-based learning effectively enhance conceptual understanding, motivation, and student achievement. Successful implementation relies on teachers’ identity as facilitators of scientific exploration, supported by continuous training, reflective communities, and the wise use of technologies such as VR and AI. In conclusion, deep learning can be implemented simply through real-world questions, local phenomena, and reflective practices. Consistent policies, authentic assessments, and cross-sector collaboration are essential to make science learning more relevant and meaningful.